2023
DOI: 10.1111/pbi.13977
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating viral vector movement enhances heterologous protein production in an established plant system

Abstract: Summary Molecular farming technology using transiently transformed Nicotiana plants offers an economical approach to the pharmaceutical industry to produce an array of protein targets including vaccine antigens and therapeutics. It can serve as a desirable alternative approach for those proteins that are challenging or too costly to produce in large quantities using other heterologous protein expression systems. However, since cost metrics are such a critical factor in selecting a production host, any system‐w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, truncating the cytosolic tail results in a loss of protein accumulation in Nicotiana benthamiana and transgenic Arabidopsis ( A. thaliana ) plants ( Wang et al 2020 ). In a recent study, we identified a few amino acid residues in the cytosolic tail that are important for PDLP5 function, but not for localization ( Wang et al 2023 ). To investigate the role of the cytosolic tail in localization, we generated a variant of PDLP5 lacking the tail sequence, fused to enhanced green fluorescent protein (EGFP) (deletion cytosolic tail [ΔCT] in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, truncating the cytosolic tail results in a loss of protein accumulation in Nicotiana benthamiana and transgenic Arabidopsis ( A. thaliana ) plants ( Wang et al 2020 ). In a recent study, we identified a few amino acid residues in the cytosolic tail that are important for PDLP5 function, but not for localization ( Wang et al 2023 ). To investigate the role of the cytosolic tail in localization, we generated a variant of PDLP5 lacking the tail sequence, fused to enhanced green fluorescent protein (EGFP) (deletion cytosolic tail [ΔCT] in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The coding sequence was cloned into pCAMBIA-1302. The Arabidopsis overexpression lines were conducted and generated by A. tumefaciens GV3101 mediated transformation [ 92 ]. Three biological replicates were used, and the experiments were performed three times.…”
Section: Methodsmentioning
confidence: 99%
“…p2300-35s-H2B-mCherry was used as a nuclear marker. The plasmid was transferred into N. benthamiana leaves using A. tumefaciens GV3101-mediated transient infiltration [ 92 ]. Subcellular localization was observed using a laser scanning confocal microscope (Zeiss LSM900) with the wavelengths of 488 (excitation)/500 to 530 nm (emission) for GFP and 561 (excitation)/590 to 640 nm (emission) for mCherry.…”
Section: Methodsmentioning
confidence: 99%